The roles of phosphorylation of signaling proteins in the prognosis of acute myeloid leukemia - Adrienn Márton; Adrienn Márton; Katalin Beáta Veres; Ferenc Erdődi; Miklós Udvardy; Árpád Illés; László Rejtő (Frontiers Media S.A., 2024)
Signaling pathways of Retinoblastoma (Rb) protein, Akt-kinase, and Erk-kinase (extracellular signal-regulated kinase) have an important role in the pathogenesis of acute myeloid leukemia. Constitutive activation of these proteins by phosphorylation contributes to cell survival by regulation of cell cycle, proliferation and proapoptotic signaling processes. According to previous data phosphorylated forms of these proteins represent a worse outcome for cancer patients. We investigated the presence of phosphorylated Rb (P-Rb), Akt (P-Akt) and Erk (P-Erk) proteins by Western blot technique using phospho-specific antibodies in bone marrow or peripheral blood samples of 69 AML patients, 36 patients with myelodysplastic syndrome (MDS) and 10 healthy volunteers. Expression level of PTEN (Phosphatase and tensin homolog) and PHLPP (PH domain and leucine-rich repeat Protein Phosphatase) phosphatases, the negative regulators of Akt kinase pathway were also examined. We tested the effect of these proteins on survival and on the correlation with known prognostic features in AML. We found 46.3% of AML patients had detectable P-Rb, 34.7% had P-Akt and 28.9% had P-Erk protein. 66.1% of patients expressing PTEN, 38.9% PHLPP, 37.2% both PTEN and PHLPP and 32.2% neither PTEN nor PHLPP phosphatases. Compared to nucleophosmin mutation (NPMc) negative samples P-Erk was significantly less in nucleophosmin mutated patients, P-Rb was significantly less in patients' group with more than 30 G/L peripheral leukocyte count by diagnosis. PHLPP was significantly present in FAB type M5. The expression of P-Rb represented significant better overall survival (OS), while P-Akt represented significantly worse event-free survival (EFS) in unfavorable cytogenetics patients. The presence of both PHLPP and PTEN phosphatases contributes to better OS and EFS, although the differences were not statistically significant. We confirmed significant positive correlation between P-Akt and PHLPP. Assessing the phosphorylation of Rb, Akt and Erk may define a subgroup of AML patients who would benefit especially from new targeted treatment options complemented the standard chemotherapy, and it may contribute to monitoring remission, relapse or progression of AML.